From Best Friends to Silent Ends: Exploring the Concepts of Ghosting in Non-Romantic Relationships - Yap, Megan Ann; Francisco, Angelo Miguel; Gopez, Christian (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Ghosting is a popular term in mass media that has continued to baffle many with its ambiguity as a dissolution strategy. Multiple studies in the past have explored ghosting within romantic relationships, examining how this dissolution strategy has impacted the two parties involved: the initiator (ghoster) and the non-initiator (ghostee). However, it has been stated that ghosting can exist outside of romantic relationships as it may also occur within friendships or even if the relationship is questionably nonexistent. The objectives of the paper seek to understand how ghosting happens within these non-romantic relationships, its effects on the initiators and non-initiators, and its possible differences when compared to romantic relationships. Semi-structured interviews were conducted through video communication platforms on thirty respondents ages 18-25 who have experienced ghosting or been ghosted by a friend. Through the use of descriptive phenomenological qualitative study, the results revealed that 1) ghosting in non-romantic relationships occurs on technology-mediated channels, 2) the initiators experienced post-dissolution feelings of regret, 3) the non-initiators experienced feelings of uncertainty, 4) ghosting a friend is more socially acceptable than ghosting a romantic partner, and, 5) ghosting is more frequent in non-romantic relationships due to the lower levels of commitment and expectations. Other recurring themes, such as the common reasons behind ghosting for the initiators and ghosting as a justifiable means of dissolving the relationship, were also found.